Fish Consumption, Erythrocyte Fatty Acids, and Preterm Birth - Klebanoff, Mark A. (2011)
OBJECTIVE: To estimate the association between fish consumption and erythrocyte omega-3 long chain polyunsaturated fatty acids and preterm birth in a high-risk cohort. METHODS: This was an ancillary study to a randomized trial of omega-3 supplementation to prevent preterm birth in women with at least one prior spontaneous preterm delivery. Dietary fish intake was assessed by questionnaire and erythrocyte fatty acids were measured at enrollment (16 to 21 completed weeks of gestation). The association between fish consumption and preterm delivery was modeled with linear and quadratic terms. RESULTS: The probability of preterm birth was 48.6% among women eating fish less than once a month and 35.9% among women eating fish more often (p<0.001). The adjusted odds ratio for preterm birth among women reporting moderately frequent fish consumption (three servings per week) was 0.60 (95% confidence interval 0.38 – 0.95), with no further reduction in preterm birth among women who consumed more than three servings of fish per week. Erythrocyte omega-3 levels correlated weakly but significantly with frequency of fish intake (Spearman r=0.22, p<0.001); women in the lowest quartile of erythrocyte omega-3 levels were more likely to report consuming less than one fish meal per month (40.3%) than were women in the highest three quartiles (26.3%, p<0.001). CONCLUSION: Moderate fish intake (up to three meals per week) prior to 22 weeks of gestation was associated with a reduction in repeat preterm birth. More than moderate consumption did not confer additional benefit. These results support the recommendations of the U.S. Food and Drug Administration and the American Congress of Obstetricians and Gynecologists for fish consumption during pregnancy.